Management as a science and art - Mrs.Rohini Gaikwad, Dr.Vinaykumar Nimbalkar, Mr.Mithun Jadhav (International Journal of Scientific Research and Management (IJSRM), 2017)
The management itself is the iterative process which revolves under itself. This is infinite time process where each iteration gives birth to new system or new concept. One has to stir so much, so that one can feel the destination has been achieved. But the rigorous efforts are to be poured to achieve maximum gain through maximum revenue and with great efficiency. To have maximum efficiency the execution of system and  time rate of each execution of every module or segment must be efficient more than 100% and it is the high level synchronizing process amongst all steps in the final product making in entire process to execute and  to trigger at perfect time to get best possible results